Global Governance - Qoraboyev, I. (Edward Elgar, 2021)
After brief introduction of global governance, this entry describes current debate on global governance through transformationalist, managerial, and critical approaches. It also elaborates on links between global governance, international law, and development
Keywords: global governance, sustainable development, United Nations, international law, managerialism